Peukateun at Rapa'i Geurimpheng in Ukee Village Geulumpang Baro District Pidie Regency - Ahmad Syai (Universitas Negeri Semarang, 2021)
Rapa'i geurimpheng is a type of traditional Acehnese music performance. This musical performance is performed by men with a cast of 8-12 people, 3-5 accompaniments and 1 syech who sounds melodious as a vocalist. The players who number 8-12 people as music presenters with attractions must learn extra to be able to put on a good show. The purpose of this study was (1) to review